Türk banka hukukunda mevduat sigortası - Alışkan, Murat (My University, 2001)
Bu çalışmada, banka hukukunun en güncel sorunlarından biri olan Mevduat Sigortası, belirli bölümler içinde toparlanarak incelenmeye çalışılmıştır. Çalışma, bir Giriş ve bir Sonuç ve Öneriler ile iki bölümden oluşmaktadır: Bankalardaki tasarruf mevduatı kamu tüzel kişiliğini haiz Tasarruf Mevduatı Sigorta Fonu tarafından sigorta edilir(BanK.m.15/ No.1). Fon'un en önemli gelir kaynağını, bankalar tarafından ödenen sigorta primleri oluşturur. Mevduat sigortası özel hukuk anlamında bir sigorta (TK.m.1263vd.) değildir; tasarrufların korunması amacıyla ihdas edilen özel bir devlet tasarrufudur. Bu sistemde mevduata sağlanan güvence Kanunen (=exlege) ve tasarruf mevduatının varlığına bağlı olarak kendiliğinden doğar. Türk hukukunda tasarruf mevduatı sigorta kapsamındadır (BanK.m. 15/ No.1, No.6,a). Sigortaya tabi olan tasarruf mevduatının kapsamı, tutarı ve diğer hususlar Kurulca (BDDK.) belirlenir (BanK.m.15/ No.6,a). 2000/ 682 sayılı Karara göre, tasarruf mevduatı hesaplarının 50 milyar Liralık kısmı sigorta kapsamındadır(m.1,m.3). Sözkonusu 50 milyar Liralık sigorta tavanı Türkiye için yüksek sayılabilir ise de, bir kriz dönemi uygulaması olmak bakımından isabetlidir. Kriz sona erdiğinde, sınırlı korumayla beklenen amaçlara ulaşılmasını sağlayacak yeni bir sigorta tavanı belirlenmesi beklenir. Küçük tasarruf sahiplerinin korunması ile piyasa disiplini tesisi arasındaki hassas dengenin kurulmasını sağlayacak olan sigorta tavanı; sektör normal yapısına döndükten sonra, mudi başına düşen ortalama tasarruf mevduatı miktarı esas alınarak ve bunun yanında bankacılık sektörünün nitelik ve özellikleri değerlendirerek belirlenmelidir. AB. mevzuatında her bir mudinin toplam mevduatının 20.000 ECU'ye kadar olan kısmı sigorta kapsamındadır. Türkiye'de mudi başına düşen ortalama tasarruf mevduatı miktarı daha düşük olsa dahi, 20.000 ECU 'nün sigorta tavanı belirlenirken dikkate alınması, AB. hukukuyla uyum bakımından isabetli olur. Bir bankanın bankacılık işlemleri yapma ve mevduat kabul etme izninin kaldırılması (BanK.m.14/ No.3; m.14/ No.5,a; m.14/ No.6) halinde yönetim ve denetimi Fon'a intikal eder(BanK.m.16/ No.1). Fon, yönetim ve denetimi kendisine intikal eden bankadaki sigortalı mevduatı doğrudan veya ilan edeceği bir banka aracılığı ile öder(BanK.m.16/ No.3). Sigortalı tasarruf mevduatı ödenmeyen mudi, doğrudan Fon'a karşı dava açabilir. Tasarruf mevduatı sahibinin bu dava hakkı Kanundan doğmaktadır.

DEPOSITS INSURANCE IN TURKISH BANKING LAW In this study, Deposits Insurance, which is one of the current biggest problems of the banking law, has been attempted to be examined through classification. The study consists of two sections and one Introduction part and one Conclusion and Suggestions part. The saving deposit accounts in the banks are insured by Savings Deposit Insurance Fund ( Banking Act m.15/ No.1). The major income of this fund is composed of savings deposit insurance premiums(Banking Act m.15/ no.2). Deposit insurance is not insurance within the scope of private law (TK. m.1263 vd.).Savings deposit insurance is a special method, a state saving that is supplied for the protection of the savings. The assurance supplied to the deposit in this system self-appears due to the existence of the savings deposit and legally (=exlege). Deposit type that is insured in the Turkish law of banking is savings deposit (Banking Act m.15/ No.1, No.6, a). According to the decision no 2000/ 682, 50 billion Turkish Liras part of the savings deposits are covered by insurance (m.1 m.3). Although the insurance base which is 50 billion Turkish Liras that is specified in the decision 2000/ 682 no m.3, could be considered as high, this amount is appropriate in terms of being a crisis period application. When this crisis period comes to an end, the determination of a new insurance base (=upper limit) in order to reach the expected goals through methods of limited coverage, is expected. The insurance base, which will enable the establishment of the sensitive balance between the protection of the small savings depositors and market discipline formation must be determined by taking base amount of the average savings per depositor and also features of banking secture after all the impacts of the crisis disappear and the sector turns back to its normal structure. We should note that in EU regulations, 20.000 ECU part of the total deposit of every depositor is covered. Although the average of the savings deposit amount per depositor in Turkey is lower, taking into account the 20.000 ECU (=minimum limit) while determining the insurance base will be appropriate in terms of complying with the EU regulations. In case that the authority of a bank to perform banking operations and accept deposit of terminated (Banking Act m.14/ No.2; m.14/ 5, a: m. 14/ No.6), the management and supervising of the bank is turned over to the Fund (Banking Act m.16/ No.2). The fund pays the insured deposit in this bank, of which management and supervising is turned over to it this way, directly or through a bank it will declare (Banking Act m.16/ No.3). The depositors of whose insured savings deposit is not paid can sue the Fund directly. This right to sue of the depositor is originated in the law, in other words the law provides the right of depositors.
Keywords: Bankacılık Hukuku Türkiye